American english file: teacher's book 2 - Latham-Koenig, Christina (Oxford University Press, 2017)
With a wide range of exciting new digital material, including all new documentaries, this new edition of American English File is still the number one course to get your students talking. American English File Second Edition retains the popular methodology developed by world-renowned authors Christina Latham-Koenig and Clive Oxenden: language + motivation = opportunity. With grammar, vocabulary, and pronunciation practice in every lesson, students are equipped with a solid foundation for successful speaking. And a new array of digital resources provides even more choice and flexibility. Students can learn in the classroom or on the move with Online Practice, iChecker, the Pronunciation App, and more.